Loss on ignition of sediment core IZN_19-31 from Lake Iznik (NW Turkey) - Renaldo Gastineau; Julia De Sigoyer; Pierre Sabatier; Stefano C Fabbri; Flavio S Anselmetti; Anne-Lise Develle; Mustafa Şahin; Serkan Gündüz; Frank Niessen; Andrea Catalina Gebhardt (PANGAEA, 2020)
The loss on ignition (LOI) analysis was performed in 2019 on the IZN19_31 Sequence, with a 10-cm sampling interval all along the sequence to estimate organic matter (OM) and carbonate proportion in the sediment, following the protocol described by Heiri et al., (2001; doi:10.1023/A:1008119611481).